Empirical Modeling Of Shear Wave Velocity And Its Effects On Non-Seismically Designed Reinforced Concrete Buildings In Penang - Tan, Chee Ghuan (2014)
In seismic engineering, shear wave velocity (vs) is one of the most important parameter for seismic microzonation and structural evaluation on the buildings with consideration of soil-structure effects (ssi). This study is focuses on the seismic microzonation of local soil and evaluates its effects on non-seismic designed reinforced concrete (rc) building using bs 8110. Multichannel analysis of surface waves (masw) surveys are carried out at fifty locations in penang in the determination of seismic response of the local soil. Seven empirical correlationsbetween vs and nspt for all soil, sand, silt and clay in unconsolidated and residual deposits were developed. The masw result shows that penang can be categorized into three site classes namely class b (very dense soil), class c (stiff soil) and class d (soft soil) according to eurocode 8. To optimize the benefits of the masw result, the indicative microzonation maps for vs30 distribution, site fundamental period and soil amplification ratio for penang were developed using an integrated geographicalinformation system and image processing software, idrisi selva.